A Technical and Behavioural Energy Efficiency Assessment of McGill Cafeteria Operations at Bishop Mountain Hall and Royal Victoria College - Cantor, Tal; Hadziosmanovic, Maida; Kim, Harriet; Marsh, Elizabeth; Secules, Chiara; Wright, Kirk; Zastavniouk, Carol (Consilience, 2015)
McGill Food and Dining Services (MFDS) have, over the past three years, progressed as a leader in sustainable practices at McGill University. Increased expectations for sustainable management have pushed Executive Chef Oliver deVolpi to assess energy efficiency at the Bishop Mountain Hall (BMH) and Royal Victoria College (RVC) cafeterias. This project aims to determine which technical and behavioural modifications should be made in the Royal Victoria College (RVC) and Bishop Mountain Hall (BMH) cafeterias in order to increase energy efficiency. Two key aspects determining energy consumption were addressed: the required energy input of the appliances and the frequency and manner of appliance usage. The technical approach assessed the sustainability of energy sources, including natural gas, electricity, and steam. The behavioural approach identified necessary improvements in mealtimes, the operation and availability of appliances, and staff practices. Using this data and appliance specification data, priority lists of suggested appliance replacements were made.